1990
DOI: 10.1093/jnci/82.12.1025
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Radon and Lung Cancer in China

Abstract: Radon has long been known to contribute to risk of lung cancer, especially in undergound miners who are exposed to large amounts of the carcinogen. Recently, however, lower amounts of radon present in living areas have been suggested as an important cause of lung cancer. In an effort to clarify the relationship of low amounts of radon with lung cancer risk, we placed alpha-track radon detectors in the homes of 308 women with newly diagnosed lung cancer and 356 randomly selected female control subjects of simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(93 citation statements)
references
References 0 publications
4
88
0
1
Order By: Relevance
“…Among them, most were excluded after abstract because they were occupational studies on miners, no case control studies, no relevant exposure or endpoint, and reviews. After assessing the full-text of the 38 relevant articles, we identified 22 eligible studies for meta-analysis (Blot et al, 1990;Schoenberg et al, 1990;Pershagen et al,1992Pershagen et al, , 1994Alavanja et al, 1994Alavanja et al, , 1999Létourneau et al, 1994;Auvinen et al, 1996;Ruosteenoja et al, 1996;Darby et al, 1998;Field et al, 2000;Sobue et al, 2000;Lagarde et al, 2001;Pisa et al, 2001;Barros-Dios et al, 2002;Wang et al, 2002;Baysson et al, 2004;Bochicchio et al, 2005;Wichmann et al, 2005;Sandler et al, 2006;Thompson et al, 2008;Wilcox et al, 2008). Seven studies were excluded for previous mete-analysis (Lubin and Boice, 1997;Pavia et al, 2003) and combined analysis in Europe, North America or China Darby et al, 2005;Krewski et al, 2005;Wang et al, 2005;Darby et al, 2006).…”
Section: Literature Searchmentioning
confidence: 99%
“…Among them, most were excluded after abstract because they were occupational studies on miners, no case control studies, no relevant exposure or endpoint, and reviews. After assessing the full-text of the 38 relevant articles, we identified 22 eligible studies for meta-analysis (Blot et al, 1990;Schoenberg et al, 1990;Pershagen et al,1992Pershagen et al, , 1994Alavanja et al, 1994Alavanja et al, , 1999Létourneau et al, 1994;Auvinen et al, 1996;Ruosteenoja et al, 1996;Darby et al, 1998;Field et al, 2000;Sobue et al, 2000;Lagarde et al, 2001;Pisa et al, 2001;Barros-Dios et al, 2002;Wang et al, 2002;Baysson et al, 2004;Bochicchio et al, 2005;Wichmann et al, 2005;Sandler et al, 2006;Thompson et al, 2008;Wilcox et al, 2008). Seven studies were excluded for previous mete-analysis (Lubin and Boice, 1997;Pavia et al, 2003) and combined analysis in Europe, North America or China Darby et al, 2005;Krewski et al, 2005;Wang et al, 2005;Darby et al, 2006).…”
Section: Literature Searchmentioning
confidence: 99%
“…Many of these studies were small and based on indirect or short-term radiation measurements, and not all studies have demonstrated such a link (Simpson & Comstock, 1983;Damber & Larsson, 1987). Most recently, a relatively large populationbased case-control study from China found no overall association between household radon exposure and lung cancer risk (Blot et al, 1990 (Henshaw et al, 1990, Lucie 1989Alexander et al, 1990). Two of these reports suggested that effects may be more pronounced for childhood leukaemias (Alexander et al, 1990;Henshaw et al, 1990).…”
mentioning
confidence: 99%
“…The detailed data collected also allowed for the calculation of risk estimates based on the other general dosimetry models used in many of the previous case -control epidemiologic studies ( Blot et al, 1990;Schoenberg et al, 1990;Pershagen et al, 1992;Pershagen et al, 1994;Alavanja et al, 1994;Alavanja et al, 1999;Letourneau et al, 1994;Auvinen et al, 1996;Ruosteenoja et al, 1996;Darby et al, 1998 ). The risk estimates obtained for the IRLCS were compared with the risk estimates that would have been obtained if the alternative models ( Table 1 ) were used.…”
Section: Field Et Almentioning
confidence: 99%
“…Most of the published case -control studies ( Blot et al, 1990;Schoenberg et al, 1990;Pershagen et al, 1992;Pershagen et al, 1994;Alavanja et al, 1994;Alavanja et al, 1999;Letourneau et al, 1994;Auvinen et al, 1996;Ruosteenoja et al, 1996;Darby et al, 1998;Kreienbrock et al, 2001 ) utilized radon measurements from one or two rooms to characterize the entire domestic exposure and did not attempt to link temporal and spatial home occupancy patterns with multiple radon measurements within a home in order to calculate retrospective cumulative radon exposures for a given time period. Because the study design of the Iowa study ( Field et al, 2000 ) included multiple radon measurements in various areas where the subject spent time and the linkage of these measurements to the subjects' spatial and temporal mobility, the data from the IRLCS provide a unique opportunity to compare various exposure methods while using a common data set.…”
Section: Introductionmentioning
confidence: 99%